Pengaruh Manajemen Perubahan Pada Kinerja Karyawan Di Playground Silungkang - Sagala, Butet; Sari, Andini Pustika; Bukhari, Ridhella; Ulfa, Sri Laila; Putra, Ramdani Bayu (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
This article discusses the impact of change management on employee performance at Playground Silangkang, an entertainment venue undergoing significant transformation in its organizational structure and operational policies. Using both quantitative and qualitative approaches, this study aims to identify how the implemented changes affect employee motivation, productivity, and job satisfaction. Data was collected through interviews, surveys, and company document analysis, and analyzed using statistical methods along with change management theories. The findings indicate that effective change management can enhance employee performance, but it requires good communication strategies, adequate training, and supportive leadership. This study provides valuable insights for companies in designing and implementing changes that can support the achievement of organizational goals and improve employee performance in the future.